Sugarcane Straw Contribution to Mitigating the Impacts of Cultivation on the Physical Quality of Oxisol - Perroni, Rafael Deberaldini [UNESP]; Fernandes, Mariele Monique Honorato [UNESP]; Coelho, Anderson Prates [UNESP]; Pinheiro, Daniel Pereira [UNESP]; Fernandes, Carolina [UNESP] (Taylor & Francis, 2022)
Sugarcane areas show a reduction in soil physical quality. However, few studies demonstrate the effect of sugarcane straw maintenance on soil physical quality along the crop cycle. This study aimed to evaluate and compare the soil physical quality in areas cultivated with sugarcane where straw was kept on soil, after the first and fourth harvests, with that of an area under native forest. Two areas cultivated with sugarcane, representative of the beginning and end of the production cycle, were evaluated in a clayey Oxisol. One area was evaluated after the first mechanical harvest (C1), while the other was evaluated after the fourth harvest (C4). These areas were compared to an area of native forest (NF). The data were subjected to multivariate principal component analysis. Agricultural areas cultivated with sugarcane showed reduction in soil physical quality compared to NF, presenting higher soil penetration resistance (SPR), soil bulk density (Sd) and microporosity (Mic). Sd was 13.7% higher in the C1 area, while in the C4 area such increase was only 5.1% compared to NF. The negative impact of sugarcane cultivation on soil physical quality is reduced after four harvests in areas with mechanical harvesting and where straw was kept on the soil, especially in the 0.00–0.20 m layer.
Keywords: Macroporosity; soil bulk density; soil conservation; soil penetration resistance; yield